Clinical Significance of Crescent Formation in IgA Nephropathy - a Multicenter Validation Study - Sehoon Park; Chung Hee Baek; Su-Kil Park; Hee Gyung Kang; Hye Sun Hyun; Eujin Park; Seung Hyeok Han; Dong-Ryeol Ryu; Dong Ki Kim; Kook-Hwan Oh; Kwon Wook Joo; Yon Su Kim; et al. (Karger Publishers, 2019)
Background/Aims: Additional validation study was warranted to confirm the clinical significance of C score, which was recently added to the Oxford classification for immunoglobulin A nephropathy (IgAN). Methods: We performed a multicenter retrospective cohort study in four hospitals in Korea. Patients who had biopsied glomeruli less than eight or inadequate follow-up information were excluded. Clinicopathologic parameters, including the degree of cellular or fibrocellular crescents, were collected and included in multivariable models for Cox regression analysis. The main outcome was a composite renal outcome, defined as a merge of progression to end-stage renal disease (ESRD) and halving of estimated glomerular filtration rate (eGFR) from baseline. Results: Among included 3,380 biopsy-confirmed IgAN patients, there were 664 (19.6%) patients with C1 and 60 (1.8%) patients with C2 scores in the study population. Although C0 and C1 patients shared similar baseline characteristics, C2 patients frequently had more clinicopathologic risk factors for poor prognosis of IgAN. Both C1 [adjusted HR 1.33 (1.11-1.58), P=0.002] and C2 [adjusted HR 2.24 (1.46-3.43), P< 0.001] scores were associated with an increased risk of the composite outcome. C2 was a strong predictive parameter associated with both progression to ESRD and halving of eGFR, whereas C1 was mainly associated with the increased risk of halving of eGFR. Notably, the proportion of crescent showed a linear association with the risk of adverse renal outcome. Conclusion: The C score in the Oxford classification is a valid predictive parameter for IgAN prognosis. Additional clinical attention is necessary for IgAN patients with identified cellular or fibrocellular crescents.